Professionalization in the Nursing and Health Technology teaching staff - Geovanis Olivares Paizan; Nadina Travieso Ramos; Tanía González García; Susana Solís Solís (Centro Provincial de Información de Ciencias Médicas, 2020)
The professionalization in the teaching staff of Nursing and Health Technology careers is the process of continuous training composed by the educational, investigative, assistance, management, bioethics and professional performance dimensions that facilitate the harmonic conjugation between "knowledge", "know how to do" and "know how to be". This professionalization constitutes a tool that can provide a way of making and a common language for the development of these professionals. That is the reason why, in this work some aspects of interest on the topic are exposed and the main results of an evaluation carried out to this training process are offered.